Beyond Short-Term Learning Gains: The Impact of Outsourcing Schools in Liberia after Three Years - Sandefur, Justin; Romero, Mauricio (Center for Global Development, 2019)
After three years, outsourcing management of public schools to private providers raised test scores by 0.21 standard deviations in math and 0.16 standard deviations in English (equivalent to 4 words per minute additional reading fluency for the cohort that started in first grade). Looking beyond learning gains, the program reduced corporal punishment (by 4.6 percentage points from a base of 51%), but increased dropout (by 3.3 percentage points from a base of 15%) and failed to reduce sexual abuse. Results vary by provider: some produced uniformly positive results, while others present stark trade-offs between learning gains and other outcomes.
Keywords: ⛔ No DOI found